Waterloo - Donaldson, J. W. A. and Becke, A. F. (London Hugh Rees, 1907)
Lured back to the army from a rural idyll, Sharpe's career culminates in the Battle of Waterloo in 1815.
Keywords: Sharpe, Richard (Fictitious character) -- Waterloo, Battle of (Belgium : 1815) -- Belgium--Waterloo